Aggressive Intervention of Pancrelipase After Pancreatectomy Prevents Deterioration of Postoperative Nutritional Status. Issue 4 (12th April 2022) - Maehira, Hiromitsu; Iida, Hiroya; Mori, Haruki; Nitta, Nobuhito; Maekawa, Takeru; Tokuda, Aya; Takebayashi, Katsushi; Kaida, Sachiko; Miyake, Toru; Tani, Masaji
Abstract : Objectives: This study aimed to investigate the effect of early administration of delayed-release high-titer pancrelipase. Methods: The medical records of 120 patients who had undergone pancreatectomy with computed tomography (CT) before and 6 months after surgery were retrospectively reviewed. Delayed-release high-titer pancrelipase were administered daily starting on postoperative day 3, which was defined as the EP group. The postoperative nutritional status and CT attenuation values of the liver were compared between the EP and control groups. Results: Thirty-three patients (28%) were categorized into the EP group. With regard to the postoperative nutritional status 6 months after surgery, the body mass index, total lymphocyte count, and Onodera's prognostic nutritional index were higher, and controlling nutritional status score was lower in the EP group than that in the control group. The CT attenuation values of the liver were not significantly different. After propensity score matching analysis, body mass index (20.7 vs 19.2, P = 0.049) and Onodera's prognostic nutritional index (47.9 vs 44.2, P = 0.045) were significantly higher, and controlling nutritional status score was significantly lower in the EP group than that in the control group (1 vs 3, P = 0.046). Conclusions: The early administration of pancrelipase after pancreatectomy improved nutritional status after pancreatectomy.